Development and Validation of Instructional Material in Astronomy - Dantic, Marshall James P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study used descriptive - developmental education research design. There are 17 science teacher education students whose currently taking Astronomy subject as major subject, and 12 faculty specialist in the field of science and professional education who served as participants of the study. Two instruments were used in gathering data, including; assessment tests and descriptive checklist. Findings revealed the following: the level of competency of the students were satisfactory before the development of the material; the developed instructional material was a module entitled “Solar: Module for Astronomy.” It was composed of different parts. It contains 19 congruent worksheets; the instructional material was perceived as “Very Useful.”; and the instructional material was perceived as “Not Difficult” to utilize. Thus, in view of these conclusions, it recommends to heighten the level of competency of the students by using developed instructional materials as references and resources; innovate and improve the developed module by adding parts and worksheets; utilize the developed instructional material as resources and references in teaching astronomy and other related fields; and maintain the difficulty of the instructional material.